Effect of pyrolysis temperature on bamboo char combustion: Reactivity, kinetics and thermodynamics. (15th November 2020) - Tong, Wei; Cai, Zelong; Liu, Qingcai; Ren, Shan; Kong, Ming
Abstract: The combustion behavior of bamboo char (BC) under pyrolysis temperatures (673–1173 K) is studied by non-isothermal thermogravimetric analysis. Results show pyrolysis temperature lowers the ignition and burnout performance of biochar. The combustion reactivity firstly increases and then decreases, and BC-973 is the best. Kinetic models of Flynn-Wall-Ozawa and Kissinger-Akahira-Sunose calculate the activation energy ( E ), integral master-plots method determines reaction equation is the reaction order that when the heating rate is less than 12 K/min, reaction orders firstly decrease and then increase with pyrolysis temperature, and reaction orders are around 1 for 24 K/min. Thermodynamic parameters (Δ H, Δ S and Δ G ) are calculated, and the prediction equations about E, Δ H, Δ S and Δ G are proposed. Meanwhile, activation energy under first order reaction and experimental equation are compared, results show that average E values under first order reaction are greater in 773–973 K, and the rest of pyrolysis temperatures are adverse. Graphical abstract: Prediction maps created using five models for As concentrations in soils at the contaminated site. Image 1 Highlights: Combustion reactivity firstly increases and then decreases. Reaction orders are around 1 at the heating rate of 24 K/min. Prediction equations of E, Δ H, Δ S and Δ G versus pyrolysis temperature are proposed. Activation energy under first order reaction and experimental equation are compared.